Identifikasi Jamur Fusarium solani yang Berasosiasi dengan Penyakit Busuk Batang pada Tanaman Buah Naga (Hylocereus sp.) Di Kecamatan Bangorejo, Kabupaten Banyuwangi - SHOLIHAH, RISMA IMROATUS; SRITAMIN, MADE; WIJAYA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.1, Januari 2019, 2019)
Identification of Fusarium solani Fungi Associated with Stem Rot Disease in Dragon Fruit Plant (Hylocereus sp.) at Bangorejo District, Banyuwangi Regency Dragon fruit plants at Banyuwangi in the maintenance process always experience disorder such as pathogenic attacks. The part of dragon fruit plant which is often attacked by pathogens is the stem which is caused the stem to rot. One type of photogenic fungus in dragon fruit plants is Fusarium solani. This fungus attacks the stem of the dragon fruit plant, so that it can cause the stem of the plant looks wilted and brown rot.The cause of stem rot disease of dragon fruit plant in Banyuwangi is not yet known exactly, thus identification in macroscopic, microscopic, and molecular need to be done. Recently, the use of molecular methods in fungi identification has increased to solve this problem. One of the molecular approaches to identify fungi is by using a device called Polymerase Chain Reaction (PCR).The result of this research showed mycelium that grown on PDA media (Potato Dextrose Agar) shaped like a thick cotton expands like a cloud, the shape of the edge of the colony is uneven, the surface color of the colony is white, the color of the bottom of the colony is white, the direction of the growth of the mycelium is to the side and the structure of the mycelium is smooth. In microscopic identification there found a long macroconidia, crescent shaped with blunt ends, 1-5 septa, microconidia shaped in round to oval, long hyphae and bersepta. The molecular identification with PCR to determine the presence of Fusarium solani mushroom by using universal primary pairs of ITS4 and ITS5 successfully amplified and produced DNA fragments measuring 560 bp.